Vitamin D in presnovki - Osredkar, Joško (Medicinski razgledi, 1996)
The object of this study was to determine reference levels of vitamin D and its metabolites in the sera of individuals with normal vitamin D metabolism. The measurements were done in compliance with the instructions for reference value determinations given by International Federation of Clinical Chemistry. The paper presents the nomenclature, physical and chemical properties, and physiology and pathologic physiology of vitamin D, as well as various diseasesassociated with changed serum levels of vitamin D and its metabolites.There follow the description of the method for determining vitaminD levels, used at the Institute of Clinical Chemistry and Clinical Biochemistry, which allows for simultaneous determinations of three vitamin D metabolites and consists of the following three phases: serum deproteinization(acetonitrile), solid phase extraction, and high pressure liquid chromatography and competitive protein binding assay. Reference individuals for our study were selected prospectively: we used blood samples obtained from them on periodic medical examinations. After excluding samples which failed to meet the set criteria of vitamin D physiology and pathologic physiology, we obtained 120 samples for calciol and calcitrol determinations, and 240 samples for calcidiol measurements. The latter were further divided into a spring and autumn subgroup. The results were analysed using a nonparametric statistical test. In addition a normal metabolite distribution (Gauss) was applies. We obtained mean 0.95 intervals with a 0.90 confidence interval for the reference values of calciol, calcidiol and calcitriol of adult males in Slovenia, considered healthy according to their vitamin D metabolism.
Keywords: vitamin; vitamini; vitamin D; presnova